2013
DOI: 10.1002/ibd.22955
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Ileal Pouch—Anal Anastomosis When Used Intentionally for Well-Defined Crohnʼs Disease

Abstract: Background Crohn’s disease (CD) is considered a contraindication to ileal pouch—anal anastomosis (IPAA). In this study, we compare outcomes of CD and ulcerative colitis (UC) patients undergoing IPAA. Methods Patients were considered to have CD before surgery based on a history of small bowel disease, perianal disease, noncrypt-associated granuloma, or pretreatment skip colonic lesions. Patients were prospectively assessed for pouchitis or CD. Postoperative CD (pouch inflammation into the afferent limb or pou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Although recent studies have shown no difference in pouch failure between CD and UC patients, this study was conducted on CD patients who had a preoperative diagnosis of UC and then received the CD diagnosis postoperatively after developing signs of CD, such as anal or pouch fistuli. Such patients are probably very different than those who are known preoperatively to have CD, and who have a significant IPAA failure rate overall [56].…”
Section: Surgical Options In CDmentioning
confidence: 97%
“…Although recent studies have shown no difference in pouch failure between CD and UC patients, this study was conducted on CD patients who had a preoperative diagnosis of UC and then received the CD diagnosis postoperatively after developing signs of CD, such as anal or pouch fistuli. Such patients are probably very different than those who are known preoperatively to have CD, and who have a significant IPAA failure rate overall [56].…”
Section: Surgical Options In CDmentioning
confidence: 97%
“…Crohn's colitis was defined by patients who had idiopathic, chronic inflammation limited to the colon, with at least two of the following: non-crypt-associated granulomas, noncontinuous areas of inflammation (''skip lesions'') in the colon, and clinical history consistent with CD [10]. Medically refractory disease was defined as ongoing evidence of clinically and histologically active colitis after optimization or intolerance to medical therapy.…”
Section: Assumptionsmentioning
confidence: 99%
“…[9] Probability of long-term remission off meds 0.779 0.65-0.95 Ref. [10], expert opinion Probability of short-term remission, then recurrent CD requiring dual therapy 0.04 0.01-0.12 Expert opinion…”
Section: Probabilitiesmentioning
confidence: 99%
See 2 more Smart Citations